The reliability and validity of a clinical 3D freehand ultrasound system. (November 2016) - Cenni, Francesco; Monari, Davide; Desloovere, Kaat; Aertbeliën, Erwin; Schless, Simon-Henri; Bruyninckx, Herman
Highlights: Ground truth objects were used to test the accuracy of a 3D freehand ultrasound system. Estimating volumes and lengths was demonstrated to be sufficiently reliable and valid. Results are dependent on the type of software implementation. Details of the current software implementation are available in an open-source software library. Graphical Abstract: Abstract: Background and Objective: Acquiring large anatomical volumes in a feasible manner is useful for clinical decision-making. A relatively new technique called 3D freehand ultrasonography is capable of this by combining a conventional 2D ultrasonography system. Currently, a thorough analysis of this technique is lacking, as the analyses are dependent on the software implementation details and the choice of measurement systems. Therefore this study starts by making this implementation available under the form of an open-source software library to perform 3D freehand ultrasonography. Following that, reliability and validity analyses of extracting volumes and lengths will be carried out using two independent motion-tracking systems. Methods: A PC-based ultrasonography device and two optical motion-tracking systems were used for data acquisition. An in-house software library called Py3DFreeHandUS was developed to reconstruct (off-line) the corresponding data into one 3D data set. Reliability and validity analyses of the entire experimental set-up were performed by estimating the volumes and lengths of ground truth objects. Ten water-filled balloons and six cross-wires were used. Repeat measurements were also performed by two experienced operators. Results: The software library Py3DFreeHandUS is available online, along with the relevant documentation. The reliability analyses showed high intra- and inter-operator intra-class correlation coefficient results for both volumes and lengths. The accuracy analysis revealed a discrepancy in all cases of around 3%, which corresponded to 3 ml and 1 mm for volume and length measurements, respectively. Similar results were found for both of the motion-tracking systems. Conclusions: The undertaken analyses for estimating volume and lengths acquired with 3D freehand ultrasonography demonstrated reliable design measurements and suitable performance for applications that do not require sub-mm and -ml accuracy.